Inside Risks Risks of Undisciplined Development. - Parnas, David L. (Communications of the ACM, 2010)
This article presents the author's views on problems in the software development industry related to the failure to set and meet standards. The author discusses regulations in engineering and how procedures can be adapted to improve the design, development, and testing of computer programs. Information is also provided on computer science students and software maintenance.